A chromatographic approach for investigating the proliferation ability of native Saccharomyces cerevisiae yeast strains under varying temperatures and ethanol concentrations - Farmakis, Lambros; Aslanidou, Panailla; Katsou, Lia; Moraiti, Nikoketa (Frontiers in Fungal Biology, 2025)
Native yeast strains have been proved to be of great importance for food industry. In the present work, two different Saccharomyces cerevisiae native yeast strains isolated from the must from Moschofilero and Agiorgitiko varieties, respectively, were studied in order to estimate the influence of temperature and ethanol concentration on their proliferation ability via asymmetric flow field-flow fractionation (AsFlFFF) technique. The growth rate of the yeast strains, was directly linked to the biomass production under these conditions and was finally investigated via the ability of AsFlFFF to separate particles according to their size. The experimental results showed that the native yeast Saccharomyces cerevisiae from the must of the Moschofilero variety has an ideal growth temperature of 15°C in the absence of alcohol but exhibits low resistance to ethanol. In contrast, yeasts from the Agiorgitiko variety exhibit resistance to 10% v/v ethanol and remain active for a longer period of time. The ability of these strains to grow under these conditions is a strong indication that they can be used as starter cultures in winemaking to improve the organoleptic characteristics of the produced wines. Yeasts from Moschofilero are suitable for starting fermentation under normal conditions, while yeasts from Agiorgitiko can be used both as starter yeasts and in ethanol environments. This study shows also that the asymmetric flow field-flow fractionation technique can be successfully used to monitor yeast growth under different experimental conditions.